2009
DOI: 10.1108/17538270910977572
|View full text |Cite
|
Sign up to set email alerts
|

Housing price volatility and its determinants

Abstract: Purpose -The purpose of this paper is to examine the housing price volatility for eight capital cities in Australia over 1987Australia over -2007. Specifically, the volatility of Australian housing and its determinants were investigated. Design/methodology/approach -An exponential-generalised autoregressive conditional heteoskedasticity (EGARCH) model was employed to analyse the volatility for eight capital cities in Australia. The Engle LM test was also utilised to examine the volatility clustering effects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…The increasing population causes the variation of the supply-demand relationship of the real estate market and affects the property prices. Lee (2009) demonstrated that the volatility of population is influential in affecting the fluctuation of housing prices. The past high volatility of population will cause an amplification effect for the current fluctuation of housing market.…”
Section: Data Collectionmentioning
confidence: 99%
“…The increasing population causes the variation of the supply-demand relationship of the real estate market and affects the property prices. Lee (2009) demonstrated that the volatility of population is influential in affecting the fluctuation of housing prices. The past high volatility of population will cause an amplification effect for the current fluctuation of housing market.…”
Section: Data Collectionmentioning
confidence: 99%
“…The UK house price volatility investigation consists of the work of Willcocks (2010), Tsai, Chen, and Ma (2010), Milles (2011b), and more recently, Begiazi and Katsiampa (2019). The Australian house price volatility has been examined by Lee (2009) and Lee and Reed (2014b); while Hossain and Latif (2009) and Lin and Fuerst (2014) studied the Canadian house price volatility. For Finland, Dufitinema (2020) has recently explored different aspects of the Finnish housing market volatility.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the housing market is determined by many closely related economic, legal, financial, institutional and political factors [1]. They can be quantified primarily in international terms, where macroeconomic factors such as GDP (gross domestic product), inflation, rates of return and availability of mortgage loans play a major role [2][3][4]. There are several factors that affect demand throughout the country, generally regardless of local variations.…”
Section: Literature Reviewmentioning
confidence: 99%